The Role of Information Technology in Islamic Religious Education Learning in Elementary Madrasahs: Integrative Analysis and Implementation Strategy - Ade Abdullah Luthfie Supriatna; Arsyad Irham Abdurrahman K.; Muhamad Syamsudin Nurfalah (Konsultan Jurnal Ilmiah Indonesia, 2026)
This article discusses the crucial role of information technology in transforming Islamic Religious Education (PAI) learning at Madrasah Ibtidaiyah (MI). Through a systematic literature review of 32 selected scholarly articles published between 2024 and 2026, this study aims to analyze the utilization, impact, challenges, and implementation strategies of digital technology in the context of PAI learning at the primary level. The review results indicate that the integration of information technology, such as e-learning platforms, digital Qur'an applications, educational social media (YouTube), and interactive presentation tools, can significantly increase student engagement, facilitate the understanding of abstract concepts, and support the development of a more contextual religious character. However, its implementation still faces complex challenges including teachers' digital literacy gap, infrastructure limitations, pedagogical resistance, and the lack of quality Islamic value-based content. This article proposes an integrative-holistic approach that combines strengthening teacher competency, developing local content, tripartite collaboration (madrasah-family-community), and sustainable supporting policies. These findings provide a theoretical contribution to the development of adaptive PAI learning models in the digital era and practical implications for education stakeholders in designing effective and character-focused digital transformation strategies at MI.